Microwave-assisted synthesis and characterization of novel chitosan-based biomaterials for pelvic organ prolapse treatment - Stangel-Wojcikiewicz, K; Piatkowski, M; Radwan-Praglowska, J; Janus, L; Matysek, D; Majka, M; Kot, M; Amrom, D; Wrobel, A (Journal of physiology and pharmacology, 2019)
Pelvic organ disorders affect up to one in four women in the United States. The prevalence of pelvic organ prolapse (POP) is increasing with each year, particularly in the setting of prolonged life expectancy and an aging population. Current treatment approaches, including polypropylene monofilaments are associated with numerous painful and worrisome side-effects. Therefore, scientists are looking for new solutions. A promising alternative to the current treatment is tissue engineering, which can be utilized to re-create support to the vagina and pelvic organs. Tissue engineering requires the use of three-dimensional scaffolds, derived from biocompatible materials. Chitosan is a natural polymer, obtained from shellfish exoskeletons. It is known for its biodegradability, lack of cytotoxicity and non-pyrogenicity. Due to the presence of free hydroxyl and amino groups, it may undergo various modifications. In this paper, we describe a new type of chitosan-based biomaterials, which can be used as a new alternative scaffold that may provide support to prolapse organs. The chitosan scaffold was obtained under microwave radiation using multifunctional amino and organic acids. We discuss the scaffold's characteristics, with an emphasis on its chemical structure and morphology. Fourier transform infrared spectroscopy (FT-IR) analysis confirmed cross-linking processes with preservation of free amino groups. Moreover, mechanical durability, the stability and swelling ability of the scaffolds in a simulated body fluid were investigated. All of the prepared scaffolds demonstrated very good antioxidant activity and biodegradability. Importantly, the biocompatibility of chitosan scaffolds was examined on human vaginal VK2/E6E7 cell line. No evidence of toxicity was documented, and the cells maintained their presence on the studied materials. These results allude to the lack of toxicity of the scaffolds, and indicate that chitosan-based scaffold should be further investigated in in vivo studies as they may be a promising alternative treatment to pelvic organ prolapse.
Keywords: antioxidancia; buněčné linie; Chitosan; chitosan; Microwaves; Cell Line; biokompatibilní materiály; Humans; Pelvic Organ Prolapse; Tissue Engineering; tkáňové inženýrství; mikrovlny; Antioxidants; prolaps pánevních orgánů; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; Biocompatible Materials; lidé